Loci controlling moisture conversion of durum wheat (Triticum turgidum sp. durum) productivity - Zaim, Meryem; Kabbaj, Hafssa; Sanchez-Garcia, Miguel; Gorjanc, Gregor; Nachit, M. M.; Al-Abdallat, Ayed; Belkadi, Bouchra; Filali-Maltouf, Abdelkarim; Kehel, Zakaria; Bassi, Filippo (2024)
Loci controlling moisture conversion of durum wheat (Triticum turgidum sp. durum) productivity.